Combination of Secang (Caesalpinia sappan L.) and Glibenclamide in Mice (Mus Muscullus) Hyperglycemia - Salsabilla, Salma Febriani Nur; Safitri, Cikra Ikhda Nur Hamidah (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Diabetes is a disease whose sufferers continue to increase in Indonesia. The International Diabetes Federation (IDF) in 2019, estimated around 463 million people with the disease. This figure is likely to continue to increase, up to 578 million in 2030 and 700 million in 2045. The use of herbal medicines is now growing, one of which comes from the secang woods (Caesalpinia sappan L.). The plant is rich in active bioactive components such as flavonoids and tannins. The flavonoids contained in secang have the ability to inhibit the enzyme α-glucosidase which plays a role in lowering the reabsorption of sugar into the blood. This study aims to determine the antihyperglycemia activity of the combination of sappang (Caesalpinia sappan L) and glibenclamamide in hyperglycemic mice. This research was carried out by providing treatment to the grouped mice. This study was experimental using a pretest-posttest with control group design. The results showed a significant difference in the average blood sugar levels of mice induced by alloxan in the group given a combination of secang and glibenclamide, namely a decrease in blood sugar levels from 227 mg/dL to 116.50 mg/dL after treatment.